2022
DOI: 10.1161/strokeaha.121.035187
|View full text |Cite
|
Sign up to set email alerts
|

Sex Difference and Rupture Rate of Intracranial Aneurysms: An Individual Patient Data Meta-Analysis

Abstract: Background and Purpose: In previous studies, women had a higher risk of rupture of intracranial aneurysms than men, but female sex was not an independent risk factor. This may be explained by a higher prevalence of patient- or aneurysm-related risk factors for rupture in women than in men or by insufficient power of previous studies. We assessed sex differences in rupture rate taking into account other patient- and aneurysm-related risk factors for aneurysmal rupture. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 32 publications
5
19
0
Order By: Relevance
“…Interestingly, even in our cohort that only consisted of wide-necked aneurysms, these findings were stable and may be considered a priori as negative prognostic predictors for complete occlusion in patients treated with SAC for wide-necked aneurysms. Furthermore, female sex was independently associated with aneurysm obliteration, which is most likely biased by the fact that aneurysm cohorts are likely to include higher numbers of women than men because female sex is a common risk factor for developing intracranial aneurysms and rupture [ 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, even in our cohort that only consisted of wide-necked aneurysms, these findings were stable and may be considered a priori as negative prognostic predictors for complete occlusion in patients treated with SAC for wide-necked aneurysms. Furthermore, female sex was independently associated with aneurysm obliteration, which is most likely biased by the fact that aneurysm cohorts are likely to include higher numbers of women than men because female sex is a common risk factor for developing intracranial aneurysms and rupture [ 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…This rate was potentially higher than the previous report. 9 This finding in this study suggests that magnetic resonance angiography should be repeated for all patients with ADPKD without ICA at regular intervals.…”
Section: Discussionmentioning
confidence: 52%
“…In addition, it is recently reported that female was associated with ICA rupture though the pathophysiology remains unclear. 9 Although no ICA had not been ruptured in all female ADPKD patients during followup in our study probably because the study size was small and regular follow-up of magnetic resonance angiography prevented and detected ICA at high risk of rupture, physicians should take more care over female patients.…”
Section: Discussionmentioning
confidence: 66%
“…Sex dichotomous effects and age are implicated in the risk factors of IA and many gene methylation rates (Vlak et al, 2011 ; Unnikrishnan et al, 2019 ; Li and Liu, 2021 ). The prevalence of IA and the risk of aneurysmal rupture in females are higher than those in males (Zuurbier et al, 2022 ). DNA methylation also shows strong sex-specific differences when individuals are exposed to harsh environments (Curtis et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%